Navigating Employee Retention: The Importance of Compensation in Phnom Penh’s Private Companies, Cambodia (American Journal of Applied Statistics and Economics, 2024)
This research addresses the critical issue of employee retention in private companies in Phnom Penh, Cambodia, specifically focusing on compensation practices. The study employs quantitative and qualitative methods, utilizing a cross-sectional approach to collect data from a sample of 335 employees. The findings reveal that many employees view their compensation package as a key factor influencing their decision to remain with their current company. However, a substantial proportion of employees expressed dissatisfaction or neutrality towards their compensation packages, signaling potential areas for improvement. The research contributes to a deeper understanding of employee preferences regarding compensation packages, thereby aiding businesses in enhancing job satisfaction and loyalty. Furthermore, the study offers practical recommendations for improving compensation practices, including enhancing transparency, conducting regular market analyses, addressing employee concerns, reassessing compensation strategies, investing in employee satisfaction, and considering employee feedback. In essence, this research comprehensively analyzes compensation practices and their impact on employee retention, offering valuable insights and actionable recommendations for private companies in Phnom Penh, Cambodia.